2022
DOI: 10.7717/peerj.14087
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide identification, phylogenetic and expression pattern analysis of Dof transcription factors in blueberry (Vaccinium corymbosum L.)

Abstract: Background DNA binding with one finger (Dof) proteins are plant-specific transcription factor (TF) that plays a significant role in various biological processes such as plant growth and development, hormone regulation, and resistance to abiotic stress. The Dof genes have been identified and reported in multiple plants, but so far, the whole genome identification and analysis of Dof transcription factors in blueberry (Vaccinium corymbosum L.) have not been reported yet. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 62 publications
2
1
0
Order By: Relevance
“…We also found that these genes were constitutively expressed in multiple tissues and organs (Figure 2). This is consistent with the experimental results of high expression levels of Dof transcription factors of blueberries and peppers (Li et al 2022;Wu et al 2016). The different expression patterns of ZmDofs in maize indicate that functional differentiation may have occurred among the ZmDof family genes during a long evolutionary process, providing new biological functions for genetic sources.…”
Section: Discussionsupporting
confidence: 90%
“…We also found that these genes were constitutively expressed in multiple tissues and organs (Figure 2). This is consistent with the experimental results of high expression levels of Dof transcription factors of blueberries and peppers (Li et al 2022;Wu et al 2016). The different expression patterns of ZmDofs in maize indicate that functional differentiation may have occurred among the ZmDof family genes during a long evolutionary process, providing new biological functions for genetic sources.…”
Section: Discussionsupporting
confidence: 90%
“…Our research found that there were multiple TFBSs in the promoter region of AvNAC genes, among which AvNAC58 was simultaneously targeted by Dof, ERF, BBR_BPC, bZIP, bHLH, TCP and MYB family for a total of 206 TFs, which was the most abundant (Figure 11 and Supplementary Table S5). Dof, AP2/ERF, bZIP, MYB and bHLH TFs play important regulatory roles in various abiotic stresses [43][44][45][46][47]. These results supported that AvNAC58 and AvNAC69 are involved in drought and salt stress responses, and they may have different mechanisms of action under various stresses.…”
Section: Roles Of Avnacs In Drought and Salt Stresssupporting
confidence: 54%
“…During this study, we identified active elements, including light responsive, hormone responsive, and abiotic stress responsive elements, within PSDOFs . These elements play crucial roles in plant growth and development, closely resembling the cis-acting elements analyzed in wheat ( Liu et al., 2020 ), lotus ( Cao et al., 2022 ), and blueberry ( Li et al., 2022b ). These studies also indicate that the composition of DOF gene promoter elements is relatively conserved, and the associated DOF genes play roles in growth, development, and stress responses.…”
Section: Discussionmentioning
confidence: 85%